Meningkatkan Mutu Manajemen Madrasah (Kajian Minat Masyarakat dan Prinsip Dasar Manajemen Lembaga Pendidikan Islam) - Ridho, Ali (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
Recently, madrasah education has begun to dim its existence, the Islamic educational institutions have become less popular among the public in terms of output and quality, so that Madrasah education generally is in second class in real condition when it is juxtaposed with educational institutions in general in Indonesia. This condition occurs because the Madrasah only think about how education continues to run regardless of the factors that can attract the public to be the main choice in processing the son or his daughter, in addition madrasah is lost identity as an Islamic educational institution that should be principled in accordance with the values- the value of Islamic educational institutions contained in the Qur'an and Hadith as the main guidance in the effort to maintain its existence. In theory of interest, the most important thing to note is the view of parents in choosing a Madrasah which if it is ranked in percentage above 50%, so the sequence is qualified, excelling, then the closeness to school / madrasah with home. While if we ranked in percentage under 50%, then the sequence is a low cost, discipline, madrasah status, easy transportation and a supportive environment to the development of children creativity. So to fulfill all efforts which become the desire of the community become the key to the emergence of these interests, but the main thing is to maintain the quality of education continuously with the appropriate management model, meaning it is in accordance with the basic concept of management of Islamic Education Institution, so that objectively society will assess and care for the existence of madrasah education together with madrasah stakeholder